EVALUASI PENYUSUNAN RENCANA STRATEGIS FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO TAHUN 2015-2019 - Elvan Sitorus; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2016)
Evaluation of Strategic Planning is a step to compare the preparation of a strategic plan that is supposed to already occurred. The purpose of this study was to describe how the strategic planning process of the Faculty of Social and Political Sciences at the University of Diponegoro and the constraints faced in their preparation. Researchers analyzed the strategic planning process and the obstacles through four stages: stage preparing, drafting stage, the stage of assessment and determination stage. Evaluation of the results of research Strategic Planning Faculty of Social and Political Sciences at the University of Diponegoro Year 2015-2019 is still encountering many obstacles on several stages of the process. In the aspect of resources must be improved quantity and quality. Coordination among the implementing other strategic plans have not been established. Data are also not accurate and was not renewed.